Importance of considering nutrient loadings from small watersheds to a lake – A case study of the Lake Shinji watershed, Shimane Prefecture, Japan - Somura, Hiroaki; Kunii, Hidenobu; Yone, Yasumichi; Takeda, Ikuo; Sato, Hirokazu (International Journal of Agricultural and Biological Engineering, 2018)
Nutrient loadings from upstream watersheds can have significant impacts on the water quality of receiving water bodies. Usually, a major river is selected as the target for water quality studies, and the impact of minor rivers tends to be ignored. It is very important to evaluate whether the impact of small rivers on the downstream water quality is negligible. River water sampling and discharge modeling using SWAT were used to analyze the contribution of small rivers to water quality in a receiving lake. From this analysis, it was determined that the inflowing total nitrogen (TN) and total phosphorus (TP) concentrations from all target rivers exceeded the lake water environmental standards set by the Ministry of the Environment. The contribution of suspended sediment (SS) and TN loads from small rivers did not vary markedly compared with their relative discharge contributions to the lake, at approximately 20%. However, the impact on TP loads to the lake from small rivers was 9.1% higher than their relative flow contributions, accounting for 28.2% of the TP loading. Thus, there is a potential to underestimate the impact of ungauged small rivers if only the major river is selected to evaluate the downstream lake water quality. Keywords: suspended sediment (SS), total nitrogen (TN), total phosphorus (TP), watershed management, SWAT model DOI: 10.25165/j.ijabe.20181105.4351 Citation: Somura H, Kunii H, Yone Y, Takeda I, Sato H. Importance of considering nutrient loadings from small watersheds to a lake – A case study of the Lake Shinji watershed, Shimane Prefecture, Japan. Int J Agric & Biol Eng, 2018; 11(5): 124–130.